2020
DOI: 10.3390/v12050564
|View full text |Cite
|
Sign up to set email alerts
|

An Elvitegravir Nanoformulation Crosses the Blood–Brain Barrier and Suppresses HIV-1 Replication in Microglia

Abstract: Even with an efficient combination of antiretroviral therapy (ART), which significantly decreases viral load in human immunodeficiency virus type 1 (HIV-1)-positive individuals, the occurrence of HIV-1-associated neurocognitive disorders (HAND) still exists. Microglia have been shown to have a significant role in HIV-1 replication in the brain and in subsequent HAND pathogenesis. However, due to the limited ability of ART drugs to cross the blood–brain barrier (BBB) after systemic administration, in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 52 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…Unfortunately, this drug had to be excluded from the treatment regimen, as it caused depression and paranoid ideation in some patients [ 153 , 154 , 155 ]. Recently, promising results were obtained by Gong et al, with their new elvitegravir nanoformulation (poloxamer-PLGA nanoformulation loaded with elvitegravir (integrase inhibitor)) [ 156 , 157 ]. Using an in vitro BBB model (co-cultured endothelial cells with astrocytes), Gong et al showed that elvitegravir nanoformulation provided improved BBB penetration and increased the suppression of HIV replication in infected human-monocyte-derived macrophages and human-monocyte-derived microglia-like cells after crossing the BBB compared to the original elvitegravir [ 156 , 157 ].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this drug had to be excluded from the treatment regimen, as it caused depression and paranoid ideation in some patients [ 153 , 154 , 155 ]. Recently, promising results were obtained by Gong et al, with their new elvitegravir nanoformulation (poloxamer-PLGA nanoformulation loaded with elvitegravir (integrase inhibitor)) [ 156 , 157 ]. Using an in vitro BBB model (co-cultured endothelial cells with astrocytes), Gong et al showed that elvitegravir nanoformulation provided improved BBB penetration and increased the suppression of HIV replication in infected human-monocyte-derived macrophages and human-monocyte-derived microglia-like cells after crossing the BBB compared to the original elvitegravir [ 156 , 157 ].…”
Section: State Of the Artmentioning
confidence: 99%
“…Recently, promising results were obtained by Gong et al, with their new elvitegravir nanoformulation (poloxamer-PLGA nanoformulation loaded with elvitegravir (integrase inhibitor)) [ 156 , 157 ]. Using an in vitro BBB model (co-cultured endothelial cells with astrocytes), Gong et al showed that elvitegravir nanoformulation provided improved BBB penetration and increased the suppression of HIV replication in infected human-monocyte-derived macrophages and human-monocyte-derived microglia-like cells after crossing the BBB compared to the original elvitegravir [ 156 , 157 ]. Using NSG mouse (NOD scid gamma mouse) and HIV-1 encephalitic (HIVE) mouse models, Gong et al demonstrated nearly twofold higher levels of elvitegravir nanoformulation in vivo in the mouse brain and a trend of decreasing HIV-1 viral load in the CNS of the HIV-1-infected mice [ 157 ].…”
Section: State Of the Artmentioning
confidence: 99%
“…AgNPs can also trigger the anti-inflammatory reaction inside microglia, which can be beneficial in neurodegenerative diseases [ 14 ]. This mechanism may also be used to treat HAND, since microglia are a targeting site for antiretroviral drug delivery [ 5 ]. Metal oxide nanoparticles, such as iron oxide, cerium oxide, and zinc oxide, are developed for imaging and decreasing oxidative stress.…”
Section: Challenges and Implications Of Biomaterials-based Drug Dementioning
confidence: 99%
“…The porous structure of polymeric nanoparticles provides a large space to encapsulate cargos. PLGA nanoparticle-based drug formulations have been shown to cross the BBB and deliver cargos into both macrophages [ 6 ] and microglia [ 5 ]. Similarly, paclitaxel-loaded PLGA-NPs were also reported to cross the BBB with the assistance of glutathione coating [ 38 ].…”
Section: Challenges and Implications Of Biomaterials-based Drug Dementioning
confidence: 99%
See 1 more Smart Citation